Development of a Saltwater Intrusion Software Using Visual Basic - Tan, Chiau Siang (2001)
Coastal aquifers play important roles for sources of water. With growing concern on groundwater resources both in term of quantity and quality, proper assessments and computation tools are becoming more important. Groundwater regional scale phenomena usually cannot be studied accurately using laboratory scale physical models; therefore mathematical tools of analysis must be applied. The advance of the computer technology should be used to solve the complicated mathematical task in solving arithmetic operations. The purpose of this study was to develop a user-friendly steady state model for simulation of saltwater intrusion into coastal aquifers. The model made use of the mathematical formulation developed by Ganfoud (1997). Two equations were derived, one for water flow, and the other for solute transport that were coupled through Darcy's velocity and concentration. In the numerical model formulation, two-dimensional Galerkin finite element approach was applied for deriving the elemental matrix equation through quadrilateral elements. The system of linear equations was solved using successive substitution employing the Gaussian elimination techniques. The whole formulation was set up by using the Visual Basic programming and Surfer graphic program (developed by Golden Software) to analyze the results. The results of intrusion were shown graphically under steady state conditions. The program has been proven to be user- friendly than other programming languages. For model verification, a hypothetical unconfined model and a physical model were used to compare the model's results with previous studies. These models applied the constant and velocity-dependent dispersion coefficient. The comparison showed a good agreement in numerical term between the proposed model and the previous ones. However, the Visual Basic program is not as powerful as the FORTRAN engineering programming and caused minor discrepancies when compared to the previous study.